PENGARUH MOBILISASI DINI TERHADAP PERISTALTIK USUS PADA PASIEN PASCA LAPARATOMI DI RSU GMIM PANCARAN KASIH MANADO (JURNAL KEPERAWATAN, 2018)
Abstract: Direct surgery that is involving the abdomen such as laparotomy can lead to the cessation of temporary intestinal movement. This is called paralytic ileus that lasts between 24-72 hours. With early mobilization that serves to stimulate intestinal peristaltic movement, patients can recover quickly from paralytic ileus. The purpose of this research is to determine the effect of early mobilization of intestinal peristaltic post-laparatomi patients. This research method is quasi experiment with pretest-posttest with control group design, the sample in this research is 20 respondents divided by 10 respondents each group. The method of data retrieval is done by non probability sampling that is incidental sampling, and the data was taken by using observation sheet. The result of research by using Mann Whitney test obtained value Ï 0,000